Analizamos y comprendemos un fragmento de la obra La Metamorfosis de Franz Kafka - Vilcamango Rojas, Julio Cesar (2020)
In the present work of professional sufficiency it has been designed and structured in three parts, of which in the first part, there is learning session elaborate according to the design of the CENEB, on the analysis and understanding of a fragment of the work, “The Metamorphosis” by Franz Kafka, and a second part that concerns theoretical support and finally, pedagogical support. The learning session entitled: we analyze and understand a fragment of the work “The Metamorphosis” by Franz Kafka. It was carried out with students of the fifth grade of secondary education, with the purpose of developing reading comprehension skills, for which an active and participatory methodology has been considered, applying the strategies of before, during and after. The corresponding scientific and pedagogical livelihoods that support the work carried out are attached.